Unmet needs of family planning and its associated factors among married women in reproductive age group, Mysuru - Anil, Deepak; D., Sunil Kumar; Vadaga, Vijaylakshmi Rao; Gopi, Arun; Murthy, M. R. Narayana (International Journal Of Community Medicine And Public Health, 2021)
Background: According to national family health survey-5 (NFHS-5), in urban Karnataka, the total unmet need was 7.3. An important concept to describe effectiveness of family planning program is unmet need for family planning. Most married women want to limit childbirth and space deliveries but are unable to use contraceptives for varying reasons leading to unmet need. To assess unmet need of family planning and its associated factors among married women in reproductive age group in Mysuru. Methods: A community based cross-sectional study was done from November 2020-January 2021 among married women in reproductive age group (18-49 years) in urban Mysuru. Sample size calculated was 162. The samples were selected by systematic random sampling and interviewed using a pre-tested semi- structured questionnaire. Data was analysed using SPSS version 23 (licensed to JSS AHER). Results: The overall unmet need was 29.01%, among this 17.3% was for spacing and 11.71% for limiting. Out of 162 females studied, around 131 had knowledge about at least one contraceptive method. Unmet need was higher in unemployed women belonging to the lower socio-economic group. Important reasons cited for not using contraceptives were family opposition, fear of side effects, negligent attitude of the women and lack of knowledge about family planning. Conclusions: Unmet need of family planning in the study area was comparatively high, therefore, routine family planning counselling, health education, and health awareness programs need to be strengthened.